Self-assembly of silica particles in a nonionic surfactant hexagonal mesophase - Sharma, Kamendra P.; Kumaraswamy, Guruswamy; Ly, Isabelle; Mondain-Monval, Olivier (Journal of Physical Chemistry B, 2009)
We investigate the process of self-assembly, and the resultant structures in composites of silica particles with a hexagonal mesophase of a nonionic surfactant and water. We report a systematic transition in behavior when the particle size is increased relative to the characteristic mesophase spacing. Water dispersible cage-like silsesquioxanes that are molecular analogues of silica particles and are smaller than the mesophase spacing swell the space between the surfactant cylinders. Silica particles comparable to the characteristic hexagonal spacing partition into the hexagonal phase and into strandlike particulate aggregates. Even larger particles phase separate from the hexagonal phase to form particulate strands that organize with a mesh size comparable to the wavelength of visible light. This self-assembly is reversible and the particles disperse by breaking up the aggregates on heating the composite into the isotropic phase. On cooling from the isotropic phase into the hexagonal, the particles are expelled from the growing hexagonal domains and finally impinge to form strandlike aggregates. Unusually, the isotropization temperature is increased in the composites as the particles nucleate the formation of the hexagonal phase.

Adsorption of nonionic surfactant on silica nanoparticles: structure and resultant interparticle interactions - Sharma, Kamendra P.; Aswal, Vinod K.; Kumaraswamy, Guruswamy (Journal of Physical Chemistry B, 2010)
Addition of nonionic surfactant, C(12)E(9), to an aqueous dispersion of charge stabilized silica nanoparticles renders particle aggregation reversible. In contrast, aggregation of the same silica particles in aqueous solutions is irreversible. We use a combination of small-angle X-ray scattering (SAXS) and contrast matching small-angle neutron scattering (SANS) to investigate interparticle interactions and microstructure in dispersions of silica particles in aqueous nonionic surfactant solutions. We show that the silica particles interact through a screened Coulombic interaction in aqueous dispersions; interestingly, this interparticle interaction is hard-sphere-like in surfactant solutions. In surfactant solutions, we show that the final surfactant-particle structure can be modeled as 14 micelles adsorbed (on average) on the surface of each silica particle. This gives rise to the short-range interparticle repulsion that makes particle aggregation reversible, and results in the hard sphere interparticle interaction potential. Finally, we show that adsorption of polyethylene imine on the surface of the silica particles prevents adsorption of surfactant micelles on the particle surface.

Volume transition of PNIPAM in a nonionic surfactant hexagonal mesophase - Jijo, V. J.; Sharma, Kamendra P.; Mathew, Renny; Kamble, Samruddhi; Rajamohanan, P. R.; Ajithkumar, Thalasseril G.; Badiger, Manohar V.; Kumaraswamy, Guruswamy (Macromolecules, 2010)
We investigate the volume transition of a thermoresponsive polymer, poly(N-isopropylacrylamide), PNIPAM, in the presence of an aqueous solution of nonionic surfactant, C(12)E(9). We combine turbidimetry with optical microscopy, NMR, and SAXS to follow the volume transition of the PNIPAM and the H(1)-isotropic transition of the surfactant/water system. Nonionic surfactants such as C(12)E(9) are known to interact weakly with PNIPAM. Accordingly, we show that there is only a small change in the volume transition temperature for the PNIPAM in isotropic micellar solutions of C(12)E(9), even for relatively high concentrations of C(12)E(9). Interestingly, once the surfactant forms an H(1) phase, there is a dramatic decrease in the coil globule transition onset temperature. We believe that this behavior results from a competition between C(12)E(9) in the H(1) phase, and PNIPAM to associate with water. When PNIPAM in the H(1) phase is cooled to low enough temperatures so as to be in the coil state, it locally disturbs the hexagonal phase ordering. Thus, we show that for PNIPAM in a weakly interacting surfactant matrix, it is the phase behavior of the matrix rather than the matrix chemistry that governs the coil globule transition. Finally, we show that in a PNIPAM copolymer with a higher LCST we observe an interesting sequence of transitions in the surfactant phase: on cooling from a high temperature free-blowing turbid globular state (similar to 75 degrees C), we enter a free-flowing translucent coil phase (similar to 47 degrees C), then a turbid gel (similar to 25 degrees C) where the copolymer is collapsed in the HI phase, and finally a low-temperature clear gel (similar to 5 degrees C) where the copolymer is in the expanded coil state.

Assembly of polyethyleneimine in the hexagonal mesophase of nonionic surfactant: effect of pH and temperature - Sharma, Kamendra P.; Choudhury, Chandan Kumar; Srivastava, Sonal; Davis, Hilda C.; Rajamohanan, P. R.; Roy, Sudip; Kumaraswamy, Guruswamy (Journal of Physical Chemistry B, 2011)
We investigate the dispersion of a pH responsive polymer, polyethyleneimine, PEI, in a hexagonal (H(1)) mesophase of a nonionic surfactant, C(12)E(9), and water, at pH ranging from basic (pH = 12.8) to acidic (pH = 1). While the C(12)E(9)/H(2)O phase behavior is independent of pH, we demonstrate that, in the PEI/C(12)E(9)/H(2)O system, changing the pH influences PEI-C(12)E(9) interactions, and thus, influences the isotropic-H(1) phase transition. With decrease in pH, there is increasing protonation of the PEI chain, and consequently, the chain extends. We show, using a combination of SAXs, optical microscopy and visual experiments, that the inclusion of PEI in a 1:1 surfactant water mixture, lowers the hexagonal-isotropic transition temperature, T. At higher pH = 12.8 T(HI) shows a pronounced decrease from SO to 13 degrees C on addition of PEI, and the PEI/C(12)E(9)/H(2)O system forms a transparent gel. At pH = 1, we observe qualitatively different behavior and an opaque gel forms below T(HI)= 25 degrees C. The isotropic-H(1) transition, in turn, influences the phase separation of PEI chains from the C(12)E(9)/H(2)O system. 2D NMR ROESY data provides evidence that there are strong surfactant PEI interactions at high pH that significantly reduce at lower pH. The NMR data is in accord with molecular dynamics simulations that show that surfactants strongly aggregate with unprotonated PEI chains, but not with fully protonated chains; thus, in this system, the pH controls a cascade of microstructural organization: increasing pH decreases chain protonation and increases polymer-surfactant interactions, resulting in suppression of the isotropic-H(1) transition to lower temperatures, thus, influencing the phase separation of PEI from the surfactant/water system.

Self-standing three-dimensional networks of nanoparticles with controllable morphology by dynamic templating of surfactant hexagonal domains - Sharma, Kamendra P.; Ganai, Anal Kumar; Sen Gupta, Sayam; Kumaraswamy, Guruswamy (Chemistry of Materials, 2011)
Assembly of nanoparticles into free-standing three-dimensional networks has implications for a wide range of applications. We show that dynamic templating of surfactant hexagonal domains is a facile technique to organize nanoparticles into a network of particulate strands. Dispersed particles (> 10 nm), independent of particle chemistry, assemble into networks, when the surfactant matrix cools into the hexagonal phase. We demonstrate assembly of inorganic, polymeric, and protein nanoparticles into networks. Where particle assembly is reversible, particles are coated with polymers that are subsequently cross-linked to stabilize the networks after surfactant removal. This technique involves near ambient temperatures and a benign water wash for template removal. The network mesh size can be varied from submicrometers to tens of micrometers by controlling the cooling rate. Particle networks can be flow-oriented prior to cross-linking, and interpenetrating networks can also be formed.
Keywords: hexagonal; macroporous; nanoparticle; self assembly; surfactant

Synthesis of functional hybrid silica scaffolds with controllable hierarchical porosity by dynamic templating - Ganai, Anal Kumar; Kumari, Sushma; Sharma, Kamendra P.; Panda, Chakadola; Kumaraswamy, Guruswamy; Sen Gupta, Sayam (Chemical Communications, 2012)
We report a facile one-pot synthesis of hierarchically porous scaffolds, with independent control over nanoparticle mesoporosity and scaffold macroporosity. Our technique combines the chemistry of mesoporous silica nanoparticles with the control afforded by dynamic templating of surfactant mesophases. These materials are readily functionalizable and allow controllable spatial variation in macroporosity.

Exclusion from hexagonal mesophase surfactant domains drives end-to-end enchainment of rod-like particles - Sharma, Kamendra P.; Ganai, Anal Kumar; Sen, Debasis; Bhagavatula L. V. Prasad; Kumaraswamy, Guruswamy (Journal of Physical Chemistry B, 2013)
Anisotropic rod-like particles assemble end-to-end when the surfactant/water matrix in which they are dispersed is cooled from the isotropic to the lyotropic hexagonal phase. We demonstrate the formation of such end-to-end assemblies for gold nanorods, which are tens of nanometers in size, as well as for micrometer-sized ellipsoidal polystyrene particles. In both cases, the particles are well-dispersed in the low-viscosity surfactant/water phase above the isotropic-H-1 transition temperature. On cooling into the H-1 phase, mesophase domains form and the particles are expelled to the isotropic phase. As the H-1 domains grow and finally impinge, the particles are localized at the domain boundaries where they reorient and assemble end-to-end. Remarkably, we observe the formation of end-to-end assemblies of gold nanorods even for volume fractions as low as 2 x 10(-6) in the initially dispersed state. The extent of particle ``enchainment'' increases with the particle concentration and with the aspect ratio of the particles.

Viscoelastic liquid from regenerated silk fibroin in the silk i conformation: a writeable and shapeable material - Kumar, Raj; Joseph, Emmanuel; Chaudhari, Atul; Nisal, Anuya; Sharma, Kamendra P. (ACS Applied Polymer Materials, 2022)
Regenerated silk fibroin (RSF) has acquired enormous attention because of its exceptional toughness, strength, and biocompatible nature. These properties make RSF a potential candidate for the fabrication of different types of materials. However, processing even a dilute aqueous solution of RSF leads to a conformational transformation from a random coil/helix-rich (silk I) to a beta-sheetrich (silk II) state. As a consequence, RSF tends to form aggregates and loses its toughness. Working in a direction to address this problem, an aqueous solution of regenerated silk fibroin has been modified with a dual layer of polyethylenimine (PEI) and a PEG-based polymer surfactant (PS). Upon freeze-drying, the RSF-polymer complex forms a solvent-free RSF bioconjugate system and exhibits a soft solid to liquid melting transition at similar to 45 degrees C. The sequential modification with PEI and PS preserves the native-like random coil conformation of RSF up to at least 8 months of storage by not allowing interchain interactions that can lead to aggregation. Rheological and small-angle X-ray scattering measurements show that the solvent-free system is viscoelastic and exhibits a higher order microstructure mediated by the packing of the PS chains, respectively. Temperature-dependent soft solid-liquid-like dual behavior offers applications in injection-based writing, compression molding, and shaping RSF bioconjugates into various types of geometries. Furthermore, the mechanical properties of the RSF bioconjugate system can be modulated by crosslinking with glutaraldehyde vapor at 50 degrees C.
Keywords: RSF liquid; RSF soft solid; silk I conformation; silk liquid; viscoelastic